Long bones from Moslem necropoles of Alexandria - Promińska, Elżbieta (Anthropological Review, 1980)
The material for this study consists of long bones of skeletons excavated at two Moslem cemeteries at Kom-el-Dikka site in Alexandria. The first cemetery, called lower necropolis, originates from the earlier stage of the Arabic Period (8th c.A.D.) the second one, called upper necropolis, dates back to 13th - 14th century A.D. From the lower necropolis 53 long bones belonging to 24 individuals of both sexes were measured. Upper necropolis supplied 661 long bones of 353 individuals. Among these members of black and of white race were distinguished. Statistical characteristics of osteometric characters are given in tables 1-3. The data pertaining to the examined material were compared to information on other earlier and modern populations from various parts of the world (see tables 4 - 6). Furthermore, the author presents results concerning sexual dimorphism in examined samples of long bones (tables 7, 8) and finaly reconstructs body height from measurements of bones. Results obtained in this respect are also compared with data on other populations.